2022
DOI: 10.3389/fpls.2022.1072621
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive resistance evaluation of 15 blueberry cultivars under high soil pH stress based on growth phenotype and physiological traits

Abstract: High soil pH is one of the main abiotic factors that negatively affects blueberry growth and cultivation. However, no comprehensive evaluation of the high soil pH tolerance of different blueberry cultivars has been conducted. Herein, 16 phenotypic and physiological indices of 15 blueberry cultivars were measured through pot experiments, and the high-pH soil tolerance coefficient (HSTC) was calculated based on these indices to comprehensively evaluate the high-soil-pH tolerance of plants. The results demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Based on the drought resistance identification of large populations, complex phenotypes increase the difficulty of investigations, and it is very important to focus on key phenotypes. In bilberry plants [ 27 ], based on statistical methods such as principal component analysis (PCA) and stepwise linear regression, 16 phenotypic and physiological indicators related to pH resistance were attributed to 7 indicators, including plant height, SOD activity and SPAD. In wheat, 12 physiological and biochemical indicators, including stomatal conductance, proline and malondialdehyde, were found to be associated with drought resistance via the use of multivariate statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the drought resistance identification of large populations, complex phenotypes increase the difficulty of investigations, and it is very important to focus on key phenotypes. In bilberry plants [ 27 ], based on statistical methods such as principal component analysis (PCA) and stepwise linear regression, 16 phenotypic and physiological indicators related to pH resistance were attributed to 7 indicators, including plant height, SOD activity and SPAD. In wheat, 12 physiological and biochemical indicators, including stomatal conductance, proline and malondialdehyde, were found to be associated with drought resistance via the use of multivariate statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…For qRT-PCR amplification, a GS AntiQ qPCR SYBR Fast Mix (Genesand Biotech Co., Ltd., Beijing, China) and a QuantStudioTM 3 System real-time system were employed. The following were the reaction conditions: 95 °C for 10 s, 60 °C for 30 s, for a total of 45 cycles; 95 °C for 15 s; 60 °C for 1 min; and 95 °C for 15 s. The GAPDH gene was chosen as the reference gene [ 73 ], and the 2 −ΔΔCt value method was used to calculate the relative expression of the related genes. The relevant primers used in this study are shown in Table S5 .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it is possible that plants need to absorb large amounts of N from the soil during their growing season, and this leads to higher carbon input for their 10.3389/ffgc.2023.1130604 morphogenesis (Eissenstat and Yanai, 1997;Wang et al, 2017). Soil pH affects the photosynthetic and osmoregulatory systems of plants (Yang et al, 2022), so it is significantly correlated with leaf and branch NSC components (Table 2).…”
Section: Factors Influencing Nsc Concentrationmentioning
confidence: 99%